A chemo-mechanical coupling model for concrete lining subjected to external sulfate attack. Issue 14 (6th December 2021) - Hou, Huiming; Hu, Dawei; Zhou, Hui; Lu, Jingjing; Zhang, Fan
Abstract: Concrete is widely used for lining structure in underground facility and unfortunately it is often attacked by coupling effects of external sulfate and triaxial compressive stress transferred from surrounding soil or rock formations. In this text, a model is developed to depict the coupling effects of mechanical loading and external sulfate attack on concrete lining. The total strain is composed of elastic strain and plastic strain characterised by modified Drucker–Prager criterion, and the deterioration of mechanical properties is related to both mechanical damage and chemical damage. The former considers microcracks generation through micromechanical operations, and the latter is defined by the molar concentration of total sulfates in concrete. A simple diffusion equation is deduced from the sulfate ions diffusion-reaction process to depict the distribution of the total sulfates in both solution and solid phase. A relationship between chemical damage and sulfates concentration is established based on experimental results. The proposed model is then implemented into COMSOL multiphysics to analyse the long-term stability of concrete lining subjected to external sulfate attack in a tunnel. The numerical results show that the simulation results match the experimental data.